Handbook of research on applied social psychology in multiculturalism - Christiansen, Bryan 1960-; Chandan, Harish C. 1947- (A volume in the Advances in psychology, mental health, and behavioral studies (APMHBS) book series, 2021)
"This book contains the recent quality research on social psychology within the context of multiculturalism, that is the manner in which a society deals with cultural diversity at the national and the community levels" - Provided by publisher